Urban Resilience Strategy in The Climate Change Governance in Makassar City, Indonesia - Ihyani Malik; Andi Luhur Prianto; Abdillah Abdillah; Zaldi Rusnaedy; Andi Annisa Amalia (Universitas Muhammadiyah Tangerang, 2021)
Urban resilience strategies need to be encouraged to support a broader, planned and integrated development process. Therefore, this article aims to look at the actualization conditions of urban policies in climate change governance in Makassar City, Indonesia. strategy is an effort to find and build a model for implementing strategies for developing urban resilience in climate change governance in Makassar City. The research method used is an explorative-qualitative method with a narrative-phenomenological approach where the data sources are primary and secondary data. Data collection through field studies and document studies. The data analysis used is an interactive model. City strategy resilience development model in climate change governance in Makassar City. The results showed that for the first time, the actual condition of Makassar City was under threat of climate change, both biophysically and socio-economically. Second, multilevel governance (MLG) as an ideal model in developing urban resilience, where the principle used is collaborative impact governance, namely building collaboration in policy making to tackle climate change. Third, decentralization as a strategy for implementing resilience, such as national conservation, which begins with the reservation of parks and protected areas. The dominant natural character is controlled under the control of the local government. The number and extent of protected areas are indicators of conservation-based programs implemented by the Makassar City Government.Strategi ketahanan perkotaan perlu di dorong untuk mendukung proses pembangunan yang lebih luas, terencana dan terintegrasi. Oleh karena itu, artikel ini bertujuan untuk mengetahui kondisi aktual strategi ketahanan perkotaan dalam tata kelola perubahan iklim di kota Makassar, Indonesia. strategi adalah upaya untuk menemukan dan membangun model strategi implementasi pengembangan kapasitas ketahanan kota dalam tata kelola perubahan iklim di Kota Makassar. Metode penelitian yang digunakan adalah metode eksploratif-kualitatif dengan pendekatan naratif-fenomenologi dimana sumber datanya adalah data primer dan sekunder. Pengumpulan data melalui studi lapangan dan studi dokumen. Analisis data yang digunakan adalah model interaktif. Model pengembangan kapasitas strategi ketahanan kota dalam tata kelola perubahan iklim di Kota Makassar. Hasil penelitian menunjukkan bahwa pertama, kondisi aktual Kota Makassar dalam ancaman perubahan iklim baik secara biofisik maupun sosial ekonomi. Kedua, multilevel governance (MLG) sebagai model ideal dalam pengembangan kapasitas ketahanan kota, dimana prinsip yang digunakan adalah tata kelola kolaboratif yaitu membangun kolaborasi dalam pembuatan kebijakan untuk menanggulangi dampak perubahan iklim. Ketiga, desentralisasi sebagai strategi penerapan kapasitas ketahanan, seperti adanya gerakan konservasi modern yang dimulai dengan pembentukan taman nasional dan kawasan lindung. Karakter alami yang dominan ditempatkan di bawah kendali pemerintah daerah. Jumlah dan luas kawasan lindung merupakan indikator keberhasilan program berbasis konservasi yang dilaksanakan oleh Pemerintah Kota Makassar.